Gaps in the Implementation of Restitution for Victims of Human Trafficking in Indonesia: Normative-Empirical and Comparative Analysis - Hidayati, Maslihati Nur; Prasetyo, Claudya Bunga Jovita (Dinasti Research, 2026)
: The crime of human trafficking in Indonesia shows an alarming escalation with 1,061 cases and 3,363 victims in 2023, while restitution paid by perpetrators only reached 13 percent of the total calculation by the LPSK in 2024. This study analyzes the legal, institutional, and procedural obstacles causing low restitution; compares restitution regulations and mechanisms in Thailand, Germany, and the United States; and formulates comprehensive recommendations for improvement. The method used is descriptive-analytical qualitative legal research with doctrinal-normative, empirical-sociological, and comparative approaches, using the theoretical framework of legal certainty, legal effectiveness, legal protection, and restorative justice. The results show that the failure of restitution implementation is systemic in all dimensions, and the three comparison countries have structural advantages in the form of mandatory restitution, the active role of prosecutors, state compensation funds, and standardized calculation formulas. The study recommends comprehensive reforms based on five pillars that integrate international best practices with the characteristics of the Indonesian legal system.